Effect of by-pass protein supplements on milk production of dairy cattle - Thapa, Puja; Pandey, Thaneshwar; Acharya, Rabin; Dhital, Bhargab (Journal of Agriculture and Natural Resources, 2019)
Bypass protein stimulates the voluntary feed intake, increase quality milk production and thereby improves the economic status of dairy cows farming. This study was conducted to assess the effect of supplementation of bypass protein on lactation performance of dairy cattle. The experiment was conducted by using 2 factorial completely randomized designs. Milk yield of individual animal was recorded daily and milk composition was recorded at fortnight interval. Results revealed that the average daily milk yield of cows fed with Heat treated soyabean cake-T1 (4.29 L) was greater than cows fed with formalin treated soyabean cake-T2 (3.56 L) followed by control group-T3 (2.62 L). . The fortnight average milk protein and fat percentages were 2.91, 2.94 and 3.18% and 5.52, 5.55 and 4.47% for T0, T1 and T2 groups respectively. The weekly average milk SNF and milk density were 8.12, 8.37 and 8.64 % and 25.67, 27.80 and 27.10%, for group T0, T1 and T2 respectively. Experiment revealed that by-pass protein supplementation to lactating animals is one of the option for improving the milk production and milk composition and suggested that further study should be conducted to precise the optimum level of bypass protein supplementation and to quantify the experimental period.